Children Rights and Mass Communication Dissemination Strategy from Nepalese Perspective - Pokharel, Prabal Raj (Socio-Economic Development Panorama, 2009)
The article solicits information and underscores thoughts and behaviour pertaining to the rights of the child as coalesced within the media system. It is primarily based upon the laws and regulations inculcated by the International Federation of Journalists. It pertains to the basic guidelines, as regards the principles prevalent upon reporting about children led issues. Likewise, it brings forth the principles of UNICEF guidelines concerned with children's rights; and the challenges that they confront during the process of undertaking a more productive children led media psychology. Media in Nepal is still in an infant stage. It needs to duly understand the cognitive, affective and psychological domain; and the rights that the children possess. Communicators from the grassroots, as well as the district or the central level seem to be lacking in terms of chalking out definite programs and actions related to the children rights. Primarily, the paper underlines the undertaking guided from upon the experiences of the International Organizations like UNICEF, and International Federation of Journalists, as to how best they have been able to carve out certain statistical tools regarding child focused dissemination strategy. Question arises, how media functions as the primary focal point of dissemination of public affairs information; and how it ought to function towards safeguard of the children's rights. The delimitation of the study is that it is exponentially expository and forbears the ethical aspects. It points out outrightly to the practices of child rights, for example, the issues of childbirths; and sex related behaviour, that media ought to generate within its context. The delimitations of the article are that it will need to uncover more case studies, generate more qualitative and quantitative research. Task lies upon what and how to conduct an in-depth study, as to what type of research ought to be undertaken, as regards association of children within the media system is concerned. This factor will eventually be of tremendous help towards eventual protection of child rights through dissemination of more advocacy and sensitization led measures, incorporating child led issues blended within the media functional tradition system. Key words: UNICEF; children right; media; TV; International Federation of Journalists; UN convention; Children and media impact; child labour Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June